Institutional and organisational change in the German rail transport sector - Carsten Gandenberger; Jonathan Hugh Köhler; Claus Doll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The paper asks how the modal shift from road to rail in the freight sector is sup-ported by institutional change. Following North (1990), institutions are understood as the "rules of the game" in the rail freight sector. Based on the literature on institutional change, four different perspectives and mechanisms can be dis-cerned: institutional design, collective action, institutional adaptation, and institu-tional diffusion. Each of these perspectives examines the situation in the German rail freight sector from a different angle. Based on this analysis, processes of institutional change and their potential impact on modal shift are discussed. Fol-lowing the railway reform, new domestic and foreign competitors of DB Cargo have entered the rail freight market with business models tailored to promising segments. At the same time, this competition has triggered a transformative or-ganisational change initiative at DB Cargo, which is currently in the process of implementation. Even though the success of this initiatives is highly uncertain, in total, the described changes are likely to result in a higher competitiveness of the sector and a stronger orientation to customer needs. Furthermore, the road freight sector has increasingly come under political pressure due to its rising GHG emissions and rail transport is increasingly seen as a viable alternative. In this respect, the recently published Master Plan for Rail Transport acts on many re-quirements of the railway sector and foresees a reduction of financial burdens, capacity extensions, and technological innovation. Overall, however, the analysis suggests that the current rate of institutional change may not be sufficient to cause the far-reaching changes necessary for a large scale transformation of the modal split of freight transport.
urn:nbn:de:0011-n-4943493; Additional information: Working Paper 3 of the study LowCarb-RFC - European Rail Freight Corridors going Carbon Neutral.
Keywords: 330